The obstructive sleep apnea syndrome (OSAS): implications for work and Occupational Health - Costa, Giovanni (La Medicina del Lavoro, 2017)
Commission Directive 2104/85/EU on driving licenses highlighted significant issues related to the Obstructive Sleep Apnea Syndrome (OSAS). Due to the high incidence of this syndrome in the general population, it is important to precisely assess its impact on work and driving performance, in terms of employee and third-party safety, general health and related social costs (errors, accidents, absenteeism, presenteism, treatments). As occupational health physicians regularly check the workers in the age group in which the incidence of OSAS is higher, they are called upon to play a strategic role in the early detection of the disease and the prescription of an appropriate therapy, as well as in monitoring the treatment effectiveness in order to assess fitness to work and/or drive. The soundness and effectiveness of the occupational health physicians’ work depend not only on their knowledge of and attention to the problem, but above all on the interaction with specialists from other disciplines, essential to arrive at a correct diagnosis and an effective treatment. Main goals of this activity are to maintain a satisfactory operating performance and to prevent possible deleterious health effects in the medium and long-term period.